2021
DOI: 10.1002/anie.202106151
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Enamide–Imine Tautomerism in the Kinetic Resolution of Tertiary Alcohols

Abstract: An efficient protocol for kinetic resolution of tertiary alcohols has been developed through an unprecedented asymmetric enamide‐imine tautomerism process enabled by chiral phosphoric acid catalysis. A broad range of racemic 2‐arylsulfonamido tertiary allyl alcohols could be kinetically resolved with excellent kinetic resolution performances (with s‐factor up to >200). This method is particularly effective for a series of 1,1‐dialkyl substituted allyl alcohols, which produced chiral tertiary alcohols that woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…[29] Thea bsolute configurations of these b-amino alcohols were assigned by X-ray crystallography of product (2R,3R)-10 a. [24] It is worth noting that only one enantiomer of the CPAcatalyst was used in this protocol to provide access to all four stereoisomers of the b-amino tertiary alcohol products,which highlighted the power of this protocol.…”
Section: Forschungsartikelmentioning
confidence: 94%
See 1 more Smart Citation
“…[29] Thea bsolute configurations of these b-amino alcohols were assigned by X-ray crystallography of product (2R,3R)-10 a. [24] It is worth noting that only one enantiomer of the CPAcatalyst was used in this protocol to provide access to all four stereoisomers of the b-amino tertiary alcohol products,which highlighted the power of this protocol.…”
Section: Forschungsartikelmentioning
confidence: 94%
“…Thea bsolute configurations of the chiral imine and enamide products were assigned by analogy to recovered (S)-1j,w hose structure was unambiguously determined by X-ray crystallography. [24] With the excellent KR results for 1,1-dialkyl-substituted allylic alcohols,w et urned our attention to 1-aryl-1-alkyldisubstituted allylic alcohols,whose disubstitutions should be easier to be differentiated in general sense (Table 3). Treatment of racemic 1o with CPA( S)-A7 (10 mol %) in benzene [25] at 25 8 8Cp rovided the imine product 2o with 98:2 er and recovered 1o with 82.5:17.5 er after 3h,corresponding to an excellent s-factor (s = 100).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Where additional comparison data is available, several other studies involving imine-type electrophiles (C=N-R) have shown the importance of including TCYP in a catalyst evaluation despite the structural similarities with TRIP. [32][33][34][35][36][37][38][39][40][41] By performing this type of analysis with similarly related electrophiles, azo compounds, [42][43][44][45][46] precedent shows TCYP to be a top performer. Continued expansion of this comparative analysis demonstrates TCYP to be effective in condensation, 47,48 halogenation [49][50][51][52] and organometallic reactions.…”
Section: Inverse Catalyst Designmentioning
confidence: 99%
“…The KR of 2-arylsulfonamido tertiary allylic alcohols 38 enabled by chiral phosphoric acid 23 catalyzed asymmetric enamide-imine tautomerism process was disclosed by Yang and co-workers in 2021 (Scheme 7a). 22 This protocol did not involve the transformation of the hydroxy group and, thus, led to the formation of two enantiomeric tertiary alcohols. Both dialkyl-and aryl,alkyl-disubstituted tertiary allylic alcohols were well resolved by this protocol, generating chiral -hydroxy enamides 38 and imines 39 with selectivity factors up to 200.…”
Section: Short Review Synthesismentioning
confidence: 99%